High-strength metal-based composite and method for producing high-strength metal-based composite
By using mixed powder of 0.3 μm-8 μm fine metal powder and 10 μm-300 μm aluminum powder, a porous preform with a volume ratio of 10-50% was solved, and the poor processability and high cost of aluminum alloy-based composite materials in the prior art were solved. Problem, high strength and good processability of aluminum alloy composites have been achieved.
Patent Information
- Application Number
- CN202380043038.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-08
- Filing Date
- 2023-11-22
- Publication Date
- 2025-01-10
AI Technical Summary
In the conventional method for producing aluminum alloy-based composite materials, it is difficult to produce a composite with a volume ratio of 50% or less and good processability, and the high pressure impregnation method has problems such as poor processability and high cost.
The porous preform is produced by high-pressure or non-pressurized impregnation method using mixed powders, including fine metal powders of 0.3 μm or more and 8 μm or less, and aluminum powders of 10 μm or more and 300 μm or less, and the filling rate is controlled between 10-50 volume %. To achieve high bending strength and good workability.
The manufacturing of high-strength metal matrix composites is realized, with a bending strength of 500-800MPa, and can be processed using super-hard tools, reducing manufacturing costs.
Smart Images

Figure BDA0005153836840000181 
Figure HDA0005153836850000011
Abstract
Description
Technical Field
[0001] The present invention relates to a metal matrix composite formed by compounding a fine powder of ceramic powder and / or metal powder functioning as a reinforcing material with a molten aluminum or aluminum alloy serving as a matrix material. Specifically, the present invention relates to a high-strength metal matrix composite having high strength and excellent workability, which is achieved by using a mixed powder containing, in addition to the fine powder, aluminum powder or aluminum alloy powder (hereinafter also referred to as "aluminum alloy powder or the like") having a larger particle size than the fine powder, and a method for producing the same. Background Art
[0002] In recent years, materials (so-called MMC) formed by compounding ceramics with aluminum or aluminum alloys, carbon fiber reinforced plastics (CFRP, Carbon Fiber Reinforced Plastics) formed by compounding resins with carbon fibers, or ceramic matrix composites (CMC, Ceramic Matrix Composites) formed by compounding ceramics with ceramic molded bodies by CVD, and composite materials formed by compounding other metal powders with aluminum have been developed and put into practical use. Among them, MMCs that have the characteristics of two different inorganic materials and use aluminum or aluminum alloys (hereinafter, referred to as aluminum alloys, etc. as representatives) as matrix materials can sometimes also make materials lightweight, and are developed as listed below and are also put into practical use. For example, they are widely used in the industry as mechanical parts and electronic substrates with desired characteristics such as light weight, high strength, high rigidity, and high heat resistance, as semiconductor liquid crystal manufacturing equipment, robot arms, gas turbine materials, power devices, etc.
[0003] In Patent Document 1, the following method is proposed: ceramic powder is added and an inorganic binder is added thereto and solidified to produce an intermediate mold (preform), and a molten aluminum alloy or the like is pressurized and infiltrated into pores outside the powder to form a composite. According to the aluminum high-pressure infiltration method, an aluminum alloy-based composite material (MMC) in which ceramic powder is uniformly distributed can be easily produced by forcibly infiltrating a molten aluminum alloy or the like into a unique intermediate mold (preform) under high pressure. The above-mentioned manufacturing method can also be applied to an aluminum alloy-based composite material (MMC) in which a powder filler formed by ceramic powder is used in a composite material.
[0004] Patent document 2 proposes a method of placing a unique intermediate molded body (preform) in which Mg powder is added to ceramic powder in a nitrogen atmosphere, and infiltrating aluminum alloy therein under non-pressurization to form a composite. The principle of this method is to improve the wettability of ceramics and Al alloys, etc. in an atmosphere of Mg and nitrogen, promote the so-called capillary phenomenon, and infiltrate the molten aluminum alloy, etc. into the voids of the preform. According to this manufacturing method, the filling rate of the ceramic can be increased by increasing the filling rate of the ceramic and reducing the voids. As a result, an aluminum alloy-based composite material (MMC) of ceramics and aluminum alloys, etc. with high physical properties such as Young's modulus, thermal conductivity, and thermal expansion coefficient can be manufactured. In addition, according to this manufacturing method, by using a preform, aluminum alloys, etc. can be infiltrated in the shape of the preform, and the MMC composite can be manufactured in a near-final manner close to the shape of the product.
[0005] In addition, aluminum alloy-based composite materials (MMC) can also be manufactured by the following casting methods other than the above-mentioned manufacturing methods. In this method, first, ceramic powders such as silicon carbide or aluminum oxide are added to a molten aluminum alloy and stirred at high speed to prepare a molten aluminum alloy containing ceramic powder, or a mixed powder of Mg is added to the ceramic powder, and an aluminum alloy is infiltrated in a nitrogen atmosphere and non-pressurized to obtain a composite, and the composite is uniformly mixed and melted to prepare a casting molten metal. Then, the prepared molten metal is cast in a conventional mold such as a sand mold, a metal mold, a lost wax mold, etc. to manufacture a composite of ceramics and aluminum alloys.
[0006] Furthermore, aluminum alloy-based composite materials (MMC) can also be manufactured by a manufacturing method using the following HIP (Hot Isostatic Pressing) method. Specifically, it is known that a powder molded body formed by mechanically alloying and coating aluminum alloy on ceramic powder is roasted and then subjected to high-pressure isotropic pressing based on HIP to manufacture a composite of ceramic powder and aluminum alloy, etc., so-called Supuremex method. In addition, as a similar method, the following method is known: a composite deposit is manufactured by spraying and depositing a molten aluminum alloy mixed with ceramic powder, etc., and since the deposit contains pores, a HIP treatment is performed to remove the pores to manufacture a composite.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent No. 6837685
[0010] Patent Document 2: Japanese Patent No. 6984926 Summary of the invention
[0011] Problem that the invention aims to solve
[0012] However, the present inventors have recognized that the above-mentioned conventional methods for producing aluminum alloy-based composite materials (MMC) each have the following problems, and that any method has room for improvement to produce an aluminum alloy-based composite material with better functionality.
[0013] In the high-pressure infiltration method described above, which is to infiltrate a molten aluminum alloy or the like under high pressure, the volume % of the powder itself of the powder filling body or preform is determined by the properties of the powder, and only a powder filling body or preform with a volume ratio exceeding 50% by volume can be manufactured. In the high-pressure infiltration method, the molten aluminum alloy or the like is infiltrated into the interstitial pores of the powder filling body or the preform, so it is difficult to reduce the volume of the metal powder and the ceramic powder, and it is difficult to increase the aluminum alloy or the like. Therefore, it is difficult to manufacture a composite with good processability and a large amount of impregnation of the aluminum alloy or the like by the high-pressure infiltration method. That is, in the method of infiltrating a molten aluminum alloy or the like under high pressure, it is impossible to manufacture a composite with a volume ratio of ceramic powder or metal powder of less than 50% and good processability. In addition, usually, as a reinforcing material for the composite, metal powder or ceramic powder of about 10 μm or more is used, so the load on the processing tool becomes large, and the aluminum alloy-based composite material (MMC) obtained by the above-mentioned high-pressure infiltration method has the problem of poor processability.
[0014] In addition, in the previously described method of compositeizing by infiltrating a molten aluminum alloy or the like into the voids of a preform under non-pressure, powder is also formed and the molten aluminum alloy or the like is infiltrated into the voids of the preform, but it is impossible to produce a preform in which the voids exceed 50 volume %, that is, an aluminum alloy-based composite material in which the powder filling rate is less than 50 volume %.
[0015] In addition, the casting method described above also has the following problems. First, in the casting method, if the content of ceramic powder in the aluminum alloy etc. becomes high, the fluidity of the molten metal deteriorates, so the upper limit of the volume content of the ceramic is usually about 30 volume %. On the other hand, in order to maintain castability, the particle size of the ceramic powder such as SiC powder used in the casting method needs to be as large as 15μm or more. Therefore, although the volume % of SiC is as low as less than 30%, the processability is low, and the obtained aluminum alloy-based composite material can only be processed with diamond tools, and the processability is poor. In addition, as another problem, the molten metal is easily entrained in air during casting, so it is difficult to obtain a composite material without defects.
[0016] In addition, in the manufacturing method using the HIP method described above, since metal powder is used as the metal raw material of the main component, the surface of the metal powder is easily oxidized during the manufacturing process, making it difficult to obtain the strength of the composite, and a complicated HIP treatment process is required, so there is a large practical problem of high cost.
[0017] Therefore, an object of the present invention is to provide a new technology regarding an aluminum alloy-based composite body and a method for producing the composite body that has high strength and good processability, can suppress manufacturing costs, is useful in industrial applicability, and has high practical value, which cannot be achieved with conventional manufacturing technologies.
[0018] Solutions for solving problems
[0019] The above object is achieved by the present invention described below. That is, the present invention provides the following high-strength metal matrix composite. The "average particle size" in the present invention is the particle size (median particle size) at which the cumulative value in the particle size distribution determined by laser diffraction / scattering method is 50%.
[0020] [1] A high-strength metal matrix composite, characterized in that it is a composite body formed by infiltrating and filling molten aluminum or aluminum alloy in a porous filler or molded body (preform), the porous filler or molded body (preform) being formed of a mixed powder, the mixed powder being formed by adding one or more aluminum / aluminum alloy powders selected from the group consisting of aluminum powders and aluminum alloy powders having an average particle size of 10 μm to 300 μm to one or more fine powders selected from the group consisting of metal powders and ceramic powders having an average particle size of 0.3 μm to 8 μm, wherein the filling rate of the fine powder in the composite body is 10 volume % to 50 volume %, and the flexural strength of the composite body is 500 MPa to 800 MPa.
[0021] Preferred embodiments of the high-strength metal matrix composite include the following.
[0022] [2] The high-strength metal matrix composite according to the above [1], wherein the metal powder constituting the fine powder of the mixed powder is any one selected from the group consisting of silicon powder, iron powder, stainless steel powder, copper powder and titanium powder, and the ceramic powder constituting the fine powder of the mixed powder is any one selected from the group consisting of alumina powder, silicon dioxide powder, aluminum borate powder, silicon carbide powder, silicon nitride powder and aluminum nitride powder, and the mixing ratio of the fine powder constituting the mixed powder to the aluminum / aluminum alloy powder is 10:90 to 90:10.
[0023] [3] The high-strength metal matrix composite according to [1] or [2], wherein the mixed powder is further added with one or more binders selected from the group consisting of silica-based binders and alumina-based organic and inorganic binders in an amount within a range of 0.5% to 10% by mass.
[0024] As another embodiment, the present invention provides a method for producing a high-strength metal matrix composite body as described below.
[0025] [4] A method for producing a high-strength metal matrix composite, characterized in that a mixed powder is obtained by adding one or more aluminum / aluminum alloy powders selected from the group consisting of aluminum powders and aluminum alloy powders having an average particle size of 10 μm to 300 μm to one or more fine powders selected from the group consisting of metal powders and ceramic powders having an average particle size of 0.3 μm to 8 μm, and then using the mixed powder to obtain a porous filled body or molded body (preform), and then the filled body or molded body (preform) is infiltrated and filled with a molten aluminum or aluminum alloy at a high pressure of 20 MPa to 200 MPa to form a composite,
[0026] A metal matrix composite having a filling rate of the fine powder of 10% by volume or more and 50% by volume or less and a bending strength of 500 MPa or more and 800 MPa or less is obtained.
[0027] [5] A method for producing a high-strength metal matrix composite, characterized in that a mixed powder is obtained by adding one or more aluminum / aluminum alloy powders selected from the group consisting of aluminum powders and aluminum alloy powders having an average particle size of 10 μm to 300 μm to one or more fine powders selected from the group consisting of metal powders and ceramic powders having an average particle size of 0.3 μm to 8 μm, and further adding magnesium powder in an amount of 0.5 parts by mass to 10 parts by mass to 100 parts by mass of the mixed powder to obtain a mixed powder containing Mg powder, obtaining a porous filled body or molded body (preform) using the mixed powder containing Mg powder, and infiltrating and filling the obtained filled body or molded body (preform) with a molten aluminum or aluminum alloy under non-pressure to form a composite,
[0028] A metal matrix composite having a filling rate of the fine powder of 10% by volume or more and 50% by volume or less and a bending strength of 500 MPa or more and 800 MPa or less is obtained.
[0029] Preferred embodiments of the method for producing a high-strength metal matrix composite according to [4] or [5] above include the following.
[0030] [6] The method for producing a high-strength metal matrix composite according to [4] or [5], wherein the metal powder constituting the fine powder of the mixed powder is any one selected from the group consisting of silicon powder, iron powder, stainless steel powder, copper powder and titanium powder, and the ceramic powder constituting the fine powder of the mixed powder is any one selected from the group consisting of alumina powder, silicon dioxide powder, aluminum borate powder, silicon carbide powder, silicon nitride powder and aluminum nitride powder, and the mixing ratio of the fine powder and the aluminum / aluminum alloy powder constituting the mixed powder is 10:90 to 90:10.
[0031] [7] The method for producing a high-strength metal matrix composite according to any one of [4] to [6] above, wherein the mixed powder further comprises one or more binders selected from the group consisting of silica-based binders and alumina-based organic and inorganic binders in an amount of 0.5% to 10% by mass.
[0032] Effects of the Invention
[0033] According to the present invention, it is possible to provide a metal matrix composite product having a volume percentage of a reinforcement material composed of metal powder and / or ceramic powder of 50 volume % or less, a bending strength of a metal matrix composite of 500 MPa or more, and good processability, which is not achievable with conventional manufacturing techniques and has high practical value. Furthermore, it is possible to provide a method for producing a metal matrix composite having the above-mentioned excellent characteristics by a simple method, which is extremely useful from the perspective of practicality in that the manufacturing cost is suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic diagram for explaining the method of manufacturing the high-strength metal matrix composite body of the present invention under non-pressurization. DETAILED DESCRIPTION
[0035] Hereinafter, preferred embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0036] As described above, conventionally, as a method for manufacturing a composite of a reinforcement material formed of metal powder and / or ceramic powder and a matrix material such as an aluminum alloy, a method of infiltrating a filled body or a molded body (preform) of the above reinforcement material with a molten aluminum alloy or the like by high pressure infiltration or non-pressure infiltration has been adopted. However, according to the research of the present inventors, in the above manufacturing method, for example, when a preform having a filling rate of 50% by volume or less of metal powder or ceramic powder is manufactured, the filling rate of the particles is low, so it is difficult to maintain the shape, and it is difficult to manufacture a preform that can withstand the high pressure infiltration method or the non-pressure infiltration method. That is, in the prior art, it is difficult to manufacture a porous preform having a void of more than 50% by volume, and therefore it is impossible to manufacture a metal matrix composite having a matrix material of more than 50% by volume of an aluminum alloy or the like by high pressure infiltration or non-pressure infiltration. In the above, the molded body (preform) is used as an example for explanation, but unlike the molded body (preform), the filling body obtained by putting the raw material powder into a metal box and vibrating the filling body is usually 50% or more, and thus, as in the case of the composite body using the molded body (preform), there is a problem of poor processability of the composite body. Hereinafter, the filling body or molded body (preform) of metal powder or ceramic powder is also referred to as "preform, etc."
[0037] The present inventors have conducted intensive research on the difficulty of producing a preform with a filling rate of 50% or less formed of metal powder or ceramic powder in the above-mentioned prior art, and found that the problem can be solved by the following structure. Specifically, the above-mentioned problem can be solved by making the preform formed of metal powder or ceramic powder, which constitutes the metal matrix composite and is infiltrated and filled with a molten aluminum alloy, etc., as described below. First, for the above-mentioned purpose, it is effective to use fine materials with an average particle size of 0.3μm or more and 8μm or less for the metal powder or ceramic powder used to form the preform. It was also found that the above-mentioned problem can be solved by using a mixed powder obtained by adding a powder of aluminum alloy or the like with an average particle size of 10μm or more and 300μm or less to the above-mentioned fine metal powder and / or ceramic powder, and producing a preform formed of the mixed powder. As described above, the "average particle size" specified in the present invention is the particle size when the cumulative value in the particle size distribution obtained by the laser diffraction / scattering method is 50%, that is, the so-called 50% median particle size.
[0038] Specifically, the inventors have found that the amount of aluminum alloy or the like constituting the metal matrix composite can be made to exceed 50% by volume by using a unique mixed material obtained by further adding a powder of aluminum alloy or the like having a larger particle size than the fine metal powder and / or ceramic powder (hereinafter also referred to as "fine powder such as metal powder") to the above-mentioned fine metal powder and / or ceramic powder, and then infiltrating the obtained preform or the like with a molten aluminum alloy or the like into the preform or the like, thereby completing the present invention. That is, the amount of aluminum alloy or the like constituting the metal matrix composite of the present invention is the sum of the amount of the powder of aluminum alloy or the like pre-added to the forming material of the preform or the like and the amount of the molten aluminum alloy or the like that is melted and infiltrated. By constituting as described above, the metal matrix composite of the present invention has a novel structure that has never been seen before, in which the aluminum alloy or the like constituting the metal matrix composite exceeds 50% by volume.
[0039] The high-strength metal matrix composite of the present invention is a composite formed by infiltrating and filling a porous preform or the like formed by mixing powders to which "powders of aluminum alloy or the like" are added with "molten aluminum alloy or the like", and therefore, part or all of the "powders of aluminum alloy or the like" may be melted and the morphology may change. Therefore, it can be said that the high-strength metal matrix composite of the present invention has a portion that cannot be directly specified by the structure or characteristics of the invention as an article. However, in this regard, the degree of melting and the state of melting of each metal powder forming the porous preform or the like generated by infiltrating and filling the complex pores of the porous preform or the like constituting the high-strength metal matrix composite of the present invention with a molten aluminum alloy or the like are of course various, and there are cases where it is impossible or generally impractical to directly specify the different microscopic melting states generated in the metal powder forming such a porous preform or the like according to the structure or characteristics of the article. Since such a situation is clear, the high-strength metal matrix composite of the present invention, which is an invention of an article, is identified as an article by a method for producing a composite body in which "a porous filler body or molded body (preformed body) formed of a mixed powder to which aluminum / aluminum alloy powder is added is infiltrated and filled with molten aluminum or aluminum alloy."
[0040] In the method for producing a metal matrix composite of the present invention, as described above, unlike the conventional method for producing a preform or the like formed only of metal powder or ceramic powder, a porous preform or the like is produced by adding a powder of an aluminum alloy or the like having a size larger than that of the fine metal powder or ceramic powder to the raw material, and then a molten aluminum alloy or the like is infiltrated into the voids of the preform or the like, thereby achieving a volume % of the aluminum alloy or the like exceeding 50%. As a result, a metal matrix composite material having excellent processability and high strength can be produced.
[0041] Specifically, the metal matrix composite of the present invention composed of the above-mentioned compounding becomes a high-strength metal matrix composite having a bending strength of 500 MPa or more, for example, 550 MPa or more, and further 700 MPa or more. More surprisingly, it was confirmed that the metal matrix composite of the present invention has good processability despite having the above-mentioned high bending strength, and can achieve processing using superhard tools that cannot be achieved with conventional composites. The above-mentioned bending strength is a value measured in accordance with JIS R1601. Specifically, it is a value measured by preparing a test piece of a specified size in accordance with JIS R1601 and performing a three-point bending test. In addition, it is a value measured at 25°C (room temperature).
[0042] According to the method for producing a metal matrix composite of the present invention, the ratio of fine powders such as metal powder and powders of aluminum alloy used in combination as a forming material of a preform or the like can be freely changed, so the ratio of fine powders such as metal powder and aluminum alloy in the final metal matrix composite material can also be freely designed. Furthermore, in the production method of the present invention, the material of fine powders such as metal powder used in the forming material of a preform or the like and the particle size determined within the range specified in the present invention can be freely designed, so a metal matrix composite having desired characteristics can be obtained. For example, according to the research of the inventors, the smaller the average particle size of fine powders such as metal powder, the greater the strength of the final metal matrix composite material. The metal matrix composite of the present invention and the method for producing the metal matrix composite are described in detail below. First, the method for producing the metal matrix composite of the present invention is described.
[0043] [Method for producing the metal matrix composite of the present invention]
[0044] As described above, the production method of the present invention is a novel production method that can make the volume % of the aluminum alloy or the like in the metal matrix composite finally obtained exceed 50% by adding the powder of the aluminum alloy or the like to the forming material of the preform or the like in advance. That is, in the present invention, unlike the conventional method of producing a metal matrix composite using a preform or the like formed only of metal powder or ceramic powder, by obtaining the metal matrix composite in the following steps, it is possible to realize that the average particle size of the fine powder of the metal powder or the like used in the raw material has an effective influence on the physical property values of the metal matrix composite finally obtained.
[0045] (1) Fine metal powder or ceramic powder
[0046] In the method for producing a metal matrix composite of the present invention, as a forming material of a porous filler or molded body (preform), one or more fine powders selected from the group consisting of metal powders and ceramic powders having an average particle size of 0.3 μm or more and 8 μm or less are used. The metal powder is not particularly limited, and examples thereof include at least one selected from the group consisting of silicon powder, iron powder, stainless steel powder, copper powder, and titanium powder. In addition, as the ceramic powder, for example, any one selected from the group consisting of alumina powder, silica powder, aluminum borate powder, silicon carbide powder, silicon nitride, and aluminum nitride powder can be cited. Moreover, when any of the above materials is used, in the present invention, as the metal powder or the ceramic powder, it is necessary to use a fine powder within the range of the average particle size specified in the present invention. Specifically, a fine powder having an average particle size within the range of 0.3 μm or more and 8 μm or less is used. The reason for setting the particle size of the metal powder or ceramic powder to 8 μm or less is that if a material larger than this is used, the interface between the metal powder or ceramic powder and the aluminum alloy or the like becomes too large after infiltration with a molten aluminum alloy or the like, and the strength of the metal matrix composite as the final product decreases. On the other hand, the reason for setting the particle size to 0.3 μm or more is that even if the particle size is smaller than this value, the strength of the obtained metal matrix composite does not change much, and when the powder is too fine, it tends to aggregate, which may impair the uniform dispersion of the reinforcing material in the preform or the like formed from the mixed powder.
[0047] (2) Aluminum powder / aluminum alloy powder
[0048] The method for producing a metal matrix composite of the present invention is characterized in that, in forming a porous filler or molded body (preform), a mixed powder is used in which aluminum powder or aluminum alloy powder having an average particle size of 10 μm or more and 300 μm or less is added to the above-mentioned fine powder such as metal powder. According to the research of the present inventors, by such a configuration, the volume ratio of the fine powder such as metal powder that functions as a reinforcing material in the metal matrix composite of the present invention can be controlled to a desired volume ratio. That is, by adding the powder of aluminum alloy etc. to the forming material of the porous preform etc., the total amount of aluminum alloy etc. in the metal matrix composite as the final product can be controlled together with the molten aluminum alloy etc. melt infiltrating into the voids of the porous preform etc. in the subsequent step. In this way, according to the present invention, by changing the ratio of one or more fine powders selected from the group consisting of metal powder and ceramic powder to the aluminum alloy etc. constituting the metal matrix composite as the final product, the desired physical property values can be achieved.
[0049] The powder of the aluminum alloy or the like used in forming the porous preform or the like that constitutes the metal matrix composite of the present invention and imparts the characteristics of the present invention uses a powder having an average particle size of 10 μm or more and 300 μm or less. When the particle size is less than 10 μm, it is easy to aggregate and it is difficult to uniformly mix with the fine powder such as the metal powder used in combination. On the other hand, when the particle size exceeds 300 μm, the powder of the aluminum alloy or the like is too large, and the uniformity of the fine powder such as the metal powder used in combination with the mixed powder is impaired, and the strength of the preform or the like may be reduced. As described below, by adding the powder of the aluminum alloy or the like having the above-mentioned specific particle size to the mixed powder for forming the porous preform or the like, the volume ratio of the metal powder and / or ceramic powder that functions as a reinforcing material constituting the metal matrix composite as the final product can be controlled.
[0050] For example, the powder volume % of the molded body (preform) made of the mixed powder of ceramic powder and / or metal powder and aluminum alloy powder used in the present invention varies depending on the particle size and mixing ratio of the powder used, but is generally 50 to 60% by volume as a whole and 40 to 60% by volume in the voids. Therefore, the volume % of the metal powder can be controlled by the molten aluminum alloy infiltrated into the voids of the porous preform and the powder of the aluminum alloy added to the molded body that gives the characteristics of the present invention. That is, if the amount of the powder of the aluminum alloy is increased, the volume % of the fine powder of the metal powder in the metal matrix composite as the final product can be reduced. As a result, according to the present invention, a good metal matrix composite product with a volume ratio of 50% or less that cannot be obtained with only metal powder and / or ceramic powder can be manufactured. For the powder of the aluminum alloy that gives the characteristics of the present invention, the amount of addition can be changed to achieve the final desired volume ratio of the metal powder and / or ceramic powder. The amount of addition is not particularly limited. In general, since the total volume % of the metal powder and / or ceramic powder used and the powder of the added aluminum alloy, etc. is 50 to 70%, the addition ratio of the powder of the aluminum alloy, etc. can be changed as needed, and the infiltration amount of the molten aluminum alloy, etc. infiltrated into the porous voids can be considered to control the overall amount of the aluminum alloy, etc.
[0051] Examples of the fine metal powder constituting the metal matrix composite of the present invention include silicon powder, iron powder, stainless steel powder, copper powder, and titanium powder. In addition, examples of the fine ceramic powder constituting the metal matrix composite of the present invention include alumina powder, silicon dioxide powder, aluminum borate powder, silicon carbide powder, silicon nitride powder, and aluminum nitride. In the present invention, one or more powders selected from the metal powders and ceramic powders listed above can be used.
[0052] The metal matrix composite of the present invention is preferably obtained by impregnating and filling a porous preform or the like formed of a mixed powder of the above-mentioned metal powder, ceramic powder and the above-mentioned aluminum alloy powder with a molten aluminum alloy in a pressurized or non-pressurized manner, and mixing the mixed powder in the following ratio. That is, the mixing ratio of the metal powder or the like fine powder to the aluminum alloy powder or the like in the mixed powder is preferably 10:90 to 90:10. When the ratio of the metal powder or the like fine powder to the above-mentioned aluminum alloy powder or the like is less than 10:90, the ratio of the metal powder or the like fine powder functioning as a reinforcing material in the metal matrix composite of the final product becomes too small, and the desired strength improvement effect may not be obtained, which is not preferred. On the other hand, when the ratio of the metal powder or the like fine powder to the aluminum alloy powder or the like exceeds 90:10, the ratio of the metal powder or the like fine powder constituting the metal matrix composite becomes too large, and the processability of the metal matrix composite of the final product deteriorates, which is not preferred.
[0053] In the metal matrix composite of the present invention, fine powders such as fine metal powders of 0.3 μm or more and 8 μm or less are used to improve the strength of the composite. On the other hand, if such fine powders are used, aggregation due to static electricity is likely to occur, so a mixed powder is used to which a relatively large powder of 10 μm to 300 μm of aluminum alloy or the like is added. By configuring in this way, a secondary effect of suppressing the aggregation of metal powders and / or ceramic powders as reinforcing materials can also be obtained, and finally a good metal matrix composite formed of uniformly dispersed metal powders and / or ceramic powders and aluminum alloy or the like can be realized. In addition, when a molten aluminum alloy or the like is infiltrated into a molded body or the like by a non-pressure infiltration method, in the prior art, if metal powders or ceramic powders with an average particle size of 1 μm or less are used in the production of porous preforms or the like, there is a problem that the pores are too small and the molten liquid is difficult to infiltrate. However, according to the technology of the present invention, the following effects are also achieved, and the above-mentioned problems can also be solved. That is, in the metal matrix composite of the present invention, by adding powder of aluminum alloy or the like having an average particle size of 10 μm or more and 300 μm or less in the preparation of a porous preform or the like, the pores become larger, so that even when the above-mentioned non-pressure infiltration method is applied, the molten aluminum alloy or the like can be easily infiltrated.
[0054] (3) Preparation of mixed powder
[0055] The mixed powder formed by adding powders of aluminum alloys and the like having an average particle size of 10 μm to 300 μm to fine powders such as metal powders as described above can be easily obtained by uniformly mixing using a conventional mixer. Next, in the present invention, a porous preform is obtained using the prepared unique mixed powder. If the fine powder as described above is used, the filling property is low, so when a molded body (preform) is obtained by methods such as press forming, CIP and sedimentation, a binder can be used in the mixed powder as needed. As a binder, inorganic binders such as ethyl silicate, silicone, water glass, inorganic binders of alumina such as aluminum alkoxide, and organic inorganic binders can be preferably used. As the amount of the binder used, it is preferably added to the mixed powder in a range of more than 0.5% and less than 10% by mass. In order to further improve the formability of the molded body (preform), in addition to the inorganic binders listed above, organic binders such as PVA and PVB can also be added.
[0056] (4) Production of preforms, etc.
[0057] The preformed body etc. made by using the mixed powder composed as described above can be baked at a temperature of about 200°C to 700°C, for example, to facilitate the subsequent operation. When using metal powder as a reinforcing material, the baking temperature is preferably 700°C or less to prevent oxidation. In addition, when adding Mg powder to the mixed powder for infiltration of a molten aluminum alloy or the like by non-pressure infiltration, the baking temperature is preferably set to 500°C or less to prevent Mg from oxidizing and degrading during baking.
[0058] (5) High-pressure infiltration of molten aluminum alloys, etc.
[0059] In the method for producing a high-strength metal matrix composite of the present invention, regardless of the high-pressure infiltration or non-pressure infiltration method, the molten aluminum alloy or the like can be infiltrated and filled in the porous preform or the like obtained as described above in a good state to obtain a metal matrix composite. In the case of using the high-pressure infiltration method, the molten aluminum alloy or the like at, for example, about 700°C to 800°C is infiltrated at a pressure of, for example, about 20 MPa to 200 MPa. At a pressure of less than 20 MPa, the pressure is too low, so there is a possibility that sufficient infiltration may not be achieved, which is not preferred. On the other hand, even if it exceeds 200 MPa, it is possible to infiltrate, but considering the energy cost and the life of the pressure vessel, a pressure of 200 MPa or less is sufficient.
[0060] (6) Non-pressurized infiltration of molten metal such as aluminum alloy
[0061] When infiltrating a molten aluminum alloy or the like by a non-pressure infiltration method, the so-called direct oxidation method (Lanxide method), it is necessary to use a mixed powder to which 0.5 to 10 parts by mass of Mg powder is added to 100 parts by mass of a total of fine powders such as metal powder and powders such as aluminum alloy. Then, a porous preform obtained using the mixed powder is infiltrated and impregnated with a molten aluminum alloy or the like, for example, at 700° C. to 900° C. under a nitrogen atmosphere and without pressure, thereby obtaining a good metal matrix composite.
[0062] Example
[0063] Hereinafter, the present invention will be described in further detail by way of examples and comparative examples of the present invention. It should be noted that the present invention is not limited to the examples.
[0064] [Example 1]
[0065] 1200g of SiC powder with an average particle size of 5μm and 800g of A6061 aluminum alloy powder with an average particle size of 25μm are added to a plastic can, and alumina balls are added and mixed for 2 hours. 100g of ethyl silicate hydrolyzate is added thereto in a manner that contains 40g in terms of SiO2, and further mixed for 30 minutes. It is added to a mold with an internal size of 200mm×200mm and pressed at a pressure of 45t. It is further calcined at 500°C for 2 hours to make a molded body (preform) containing SiC powder and aluminum alloy powder. The obtained molded body is placed in a metal mold, and the molten A6061 aluminum alloy melted at 750°C is poured into it, and it is infiltrated into the preform at a pressure of 100MPa to cast a composite.
[0066] The composite obtained by the above method is an aluminum alloy-based composite with SiC fine powder as 30 volume % and the remainder as 70 volume %. A test piece of a specified size for measurement was cut out from the obtained composite, and the bending strength of the composite was measured at room temperature according to JIS R1601 using the test piece. The same method was used for the other examples. The measurement result was 740 MPa, which is quite high in strength. In addition, it was confirmed that the obtained composite had good processability and could be processed with superhard tools.
[0067] [Example 2]
[0068] Add 1200g of SiC powder with an average particle size of 5μm and 800g of A6061 aluminum powder with an average particle size of 25μm, which are the same as those used in Example 1, and add 40g of Mg powder with an average particle size of 50μm, and mix for 2 hours in the same manner as in Example 1. Add a liquid of silicone resin (trade name: KR-220L, manufactured by Shin-Etsu Chemical Co., Ltd.) dissolved in isopropyl alcohol in an amount of 30g% converted to SiO2, and mix for 30 minutes. Press-form and bake it in the same manner as in Example 1 to produce a molded body (preform). Cut a preform of 100mm×100mm×30mm in size from the molded body. Then, as Figure 1 As shown in FIG. 1 , under non-pressurized conditions, the preform 1 is infiltrated and filled with a molten aluminum 2 of the A6061 series and composited to produce an aluminum alloy matrix composite. Specifically, Figure 1 As shown, the preform 1 and A6061 aluminum 2 are placed in a carbon container 4, which is placed in a furnace in a nitrogen atmosphere, heated at a rate of 100°C / hour, maintained at 780°C for 2 hours, and then the composite is taken out. Figure 1 3 in the figure indicates a permeation path made of the same material as that of the preform 1. The composite taken out was processed into a measurement form, and the physical property values were measured in the same manner as in Example 1.
[0069] The composite obtained in Example 2 is also an aluminum alloy-based composite body with 30 volume % of SiC fine powder and 70 volume % of aluminum alloy, as in Example 1. The bending strength measured by the same method as in Example 1 is 650 MPa, which is a high-strength composite body. In addition, the obtained composite body has good processability and can be processed with superhard tools.
[0070] [Example 3]
[0071] 800 g of SiC powder having an average particle size of 3 μm and 1200 g of A1050 aluminum alloy powder having an average particle size of 30 μm were further mixed with 100 g of ethyl silicate hydrolyzate in a manner that contained 40 g in terms of SiO2, and a preform containing SiC powder and aluminum alloy powder was prepared in the same manner as in Example 1. Then, the obtained preform was infiltrated with a molten A1050 aluminum alloy under high pressure by the same operation as in Example 1 to obtain the composite of this example.
[0072] The physical properties of the composite obtained above were measured, and the results showed that it was an aluminum alloy-based composite with SiC fine powder as 20 volume % and the balance as 80 volume %. The bending strength measured by the same method as in Example 1 was 700 MPa, which was a composite with a relatively high strength. In addition, the obtained composite had good processability and could be processed with superhard tools.
[0073] [Example 4]
[0074] 1200g of metal silicon powder with an average particle size of 5μm was mixed with 200g of A6061 aluminum alloy powder with an average particle size of 25μm in the same manner as in Example 1, and 100g of ethyl silicate hydrolyzate was added thereto in an amount of 40g in terms of SiO2, and the mixture was further mixed for 30 minutes. Using the obtained mixture, a molded body (preform) was prepared by the same operation as in Example 1. Then, using the obtained preform, a molten A6061 aluminum alloy was high-pressure infiltrated by the same operation as in Example 1 to obtain a composite.
[0075] The physical properties of the composite obtained above were measured. The composite was an aluminum alloy-based composite with 25 volume % of silicon powder and 75 volume % of aluminum alloy powder. The bending strength measured by the same method as in Example 1 was 580 MPa, indicating high strength. In addition, the composite obtained had good processability and could be processed with a superhard tool.
[0076] [Comparative Example 1]
[0077] 100 g of ethyl silicate hydrolyzate solution was added to 2000 g of SiC powder having an average particle size of 14 μm larger than that specified in the present invention in the same manner as in Example 1 so as to contain 40 g in terms of SiO2, and a preform was prepared using the mixed material. Then, the obtained preform was impregnated with a molten aluminum alloy similar to that used in Example 1 to prepare a composite. Comparative Example 1 differs from the present invention in that the average particle size of the SiC powder is larger than that specified in the present invention and that aluminum powder is not used in the mixture of the raw materials.
[0078] The physical properties of the composite obtained above were measured. As a result, the composite obtained was a composite of 55 volume % SiC and 45 volume % aluminum alloy. The bending strength measured by the same method as in Example 1 was 320 MPa, which was the same as that of a general aluminum alloy, and it was confirmed that it was not a high-strength composite. In addition, the composite obtained had poor machinability and could not be machined with a superhard tool, so it was machined with a diamond end mill.
[0079] [Comparative Example 2]
[0080] The composite of this example was prepared by the same operation as in Example 1, except that a mixture of 1200 g of SiC powder having an average particle size greater than 14 μm specified in the present invention and 800 g of 6061 aluminum alloy powder having an average particle size of 25 μm was used. The physical properties of the composite obtained were a composite of 28% by volume of SiC and 72% by volume of aluminum. The bending strength measured by the same method as in Example 1 was 330 MPa, which was the same as that of a general aluminum alloy and was not a high-strength composite. In addition, the composite obtained had poor machinability and could not be machined with superhard tools, and needed to be machined with a diamond end mill.
[0081] [Comparative Example 3]
[0082] A molded body (preform) was prepared by the same operation as in Example 1 except that a mixture of 1200 g of SiC powder having an average particle size greater than 22 μm specified in the present invention and 800 g of A6061 aluminum alloy powder having an average particle size of 25 μm was used. Then, the preform obtained above was infiltrated with a molten A6061 aluminum alloy by the same operation as in Example 1 to obtain a composite body of this example.
[0083] The physical properties of the obtained composite were measured, and the results showed that it was an aluminum-based composite with 31 volume % of SiC powder and the balance of 69 volume %. In addition, the bending strength measured by the same method as in Example 1 was 410 MPa, which was lower than that of the composites of Examples 1 to 4, and was a bending strength of the general aluminum level, and was not a high-strength composite. In addition, the obtained composite had poor processability and could only be processed with a diamond tool.
[0084] [Comparative Example 4]
[0085] 800 g of A6061 aluminum alloy powder with an average particle size of 25 μm is used in 1200 g of metal silicon powder with an average particle size greater than 45 μm specified in the present invention, and a molded body (preformed body) is made by the same operation as in Example 1. The A6061 aluminum alloy is infiltrated into the preformed body by the same operation as in Example 1 to obtain a composite body.
[0086] The physical properties of the obtained composite were measured, and the composite was 29% by volume of 45 μm metal silicon powder and 71% by volume of A6061 aluminum alloy. The bending strength measured by the same method as in Example 1 was 270 MPa, indicating a low strength composite.
[0087] [Comparative Example 5]
[0088] An ingot of a composite material of 30 volume % SiC powder / 70 volume % aluminum manufactured by Duralcan, USA, was used. The ingot was melted at 730°C and cast in a sand mold to produce a composite body of 200 mm×200 mm×50 mm (thickness). Then, a test piece for measurement was cut out in the same manner as used in Example 1, and the bending strength was measured in the same manner. As a result, the bending strength of the composite body obtained above was 380 MPa, which was low in strength. In addition, the processability was poor and it could only be processed with a diamond tool.
[0089] [Summary of evaluation results]
[0090] Table 1 summarizes the preparation conditions of the composites of the embodiments and comparative examples and the evaluation results of the obtained composites. Regarding the evaluation of processability, the composites that can be processed using superhard tools are evaluated as "good", and the composites that cannot be processed using superhard tools and can only be processed using diamond tools are evaluated as "poor". In Comparative Example 5, a commercially available composite material (commercially available product) of SiC powder and aluminum metal was used. In addition, in Example 2, the molten aluminum alloy was infiltrated into the preform in a non-pressurized manner. In the examples other than Example 2, the molten aluminum alloy was infiltrated and filled into the preform at a high pressure of 100 MPa.
[0091] [Table 1]
[0092] Table 1: Preparation conditions of the composites of the examples and comparative examples and evaluation results of the obtained composites
[0093]
[0094] Description of Reference Numerals
[0095] 1: Preform
[0096] 2: Aluminum alloy, etc.
[0097] 3: Permeation channel made of the same material as the preform
[0098] 4: Carbon container
Claims
1. A high-strength metal matrix composite, characterized in that: It is a composite body formed by infiltrating and filling molten aluminum or aluminum alloy in a porous filler or molded body (preform), wherein the porous filler or molded body (preform) is formed by a mixed powder, wherein the mixed powder is formed by adding one or more aluminum / aluminum alloy powders selected from the group consisting of aluminum powder and aluminum alloy powder with an average particle size of 10 μm to 300 μm to one or more fine powders selected from the group consisting of metal powder and ceramic powder with an average particle size of 0.3 μm to 8 μm, and for the composite body, the filling rate of the fine powder is 10 volume % to 50 volume %, and the bending strength of the composite body is 500 MPa to 800 MPa.
2. The high-strength metal matrix composite according to claim 1, wherein: The metal powder constituting the fine powder of the mixed powder is any one selected from the group consisting of silicon powder, iron powder, stainless steel powder, copper powder and titanium powder, and the ceramic powder constituting the fine powder of the mixed powder is any one selected from the group consisting of alumina powder, silica powder, aluminum borate powder, silicon carbide powder, silicon nitride powder and aluminum nitride powder. Furthermore, the mixing ratio of the fine powder constituting the mixed powder and the aluminum / aluminum alloy powder is 10:90 to 90:
10.
3. The high-strength metal matrix composite according to claim 1 or 2, wherein: Furthermore, the mixed powder is obtained by adding one or more binders selected from the group consisting of silica-based binders and alumina-based organic and inorganic binders in an amount within a range of 0.5% to 10% by mass.
4. A method for manufacturing a high-strength metal matrix composite, characterized in that: A mixed powder is obtained by adding one or more aluminum / aluminum alloy powders selected from the group consisting of aluminum powders and aluminum alloy powders having an average particle size of 10 μm to 300 μm to one or more fine powders selected from the group consisting of metal powders and ceramic powders having an average particle size of 0.3 μm to 8 μm, and using the mixed powder to obtain a porous filler or molded body (preform), and the obtained filler or molded body (preform) is infiltrated and filled with a molten aluminum or aluminum alloy at a high pressure of 20 MPa to 200 MPa to compound the filler or molded body (preform), A metal matrix composite having a filling rate of the fine powder of 10 volume % or more and 50 volume % or less and a bending strength of 500 MPa or more and 800 MPa or less is obtained.
5. A method for producing a high-strength metal matrix composite, characterized in that: A mixed powder is obtained by adding one or more aluminum / aluminum alloy powders selected from the group consisting of aluminum powder and aluminum alloy powders with an average particle size of 10 μm to 300 μm to one or more fine powders selected from the group consisting of metal powder and ceramic powder with an average particle size of 0.3 μm to 8 μm, and further adding magnesium powder in a range of 0.5 mass parts to 10 mass parts to 100 mass parts of the mixed powder to obtain a mixed powder containing Mg powder, and using the mixed powder containing Mg powder to obtain a porous filling body or molded body (preform), and in the obtained filling body or molded body (preform), infiltrating and filling a molten aluminum or aluminum alloy under non-pressure to make it composite, A metal matrix composite having a filling rate of the fine powder of 10 volume % or more and 50 volume % or less and a bending strength of 500 MPa or more and 800 MPa or less is obtained.
6. The method for producing a high-strength metal matrix composite according to claim 4 or 5, wherein: The metal powder constituting the fine powder of the mixed powder is any one selected from the group consisting of silicon powder, iron powder, stainless steel powder, copper powder and titanium powder, and the ceramic powder constituting the fine powder of the mixed powder is any one selected from the group consisting of alumina powder, silica powder, aluminum borate powder, silicon carbide powder, silicon nitride powder and aluminum nitride powder. Furthermore, the mixing ratio of the fine powder constituting the mixed powder and the aluminum / aluminum alloy powder is 10:90 to 90:
10.
7. The method for producing a high-strength metal matrix composite according to claim 4 or 5, wherein: The mixed powder may further contain one or more binders selected from the group consisting of silica-based binders and alumina-based organic and inorganic binders in an amount of 0.5% to 10% by mass.